Katrina's Imprint : Race and Vulnerability in America - Anglin, Roland; Dowd, Jeffrey; O'Neill, Karen M.; Wailoo, Keith (Book collections on Project MUSE., 2010)
Katrina's Imprint highlights the power of this seminal American event and its continuing reverberations in contemporary politics, culture, and public policy. Published on the fifth anniversary of Hurricane Katrina, this multidisciplinary volume reflects on how history, location, access to transportation, health care, and social position feed vulnerability and resilience and shape prospects for the recovery of New Orleans and the Gulf region. A multifaceted, wide-ranging case study of race in America, this book offers an argument for why we cannot wait for the next disaster before we apply the lessons we have learned from Katrina. --Book Jacket.